PROBLEMS OF TRANSLATING HUMOR ACROSS CULTURES - Khamidova Yodora Khamidovna (International Journal of Literature and Language Studies, 2026)
Humor is one of the most challenging things to translate since it is so ingrained in language, culture, and social situation. This research investigates the main challenges encountered when translating humor across cultures and investigates the methods translators use to maintain the comic impact. The study concentrates on wordplay, linguistic humor, cultural allusions, idiomatic expressions, and context-dependent jokes that frequently lose their meaning when translated into another language. The study uses a comparative analysis of humorous texts translated between English and Uzbek to pinpoint typical translation problems and gauge the efficacy of several translation methods, such as adaptation, substitution, paraphrasing, and omission. According to the findings, cultural variations, the absence of similar statements, and differing audience expectations have a major influence on the translation of humor. The research indicates that effective humor translation calls for a thorough grasp of the source and target cultures in addition to linguistic skill. The findings add to the body of knowledge in translation studies by showcasing workable methods for improving intercultural communication and conquering cross-cultural challenges in humor translation.